Magnifico - De Los Reyes, Maryo J.; Yamamoto, Michiko; Manio, Jiro; Tolentino, Lorna; MartiI?nez, Albert; Romero, Gloria 1933-; Rodriguez, Celia; Sevilla, Violeta C.; Labad, Lutgardo; Violett Films, Inc.; GMA Films ([Manila, Philippine] Unitel Picture International Distributed by GMA Films, 2003)
When Miong, Magnifico's brother loses his scholarship in Manila, his parents also loses all their hope in having a better life. Added to Miong's failure, there's their youngest sibling Helen who has cerebral palsy and who hasn't spoken yet. It seems fate is playing a prank on them because the grandma, Magda, is also diagnosed to have a terminal illness. Magnifico's sympathetic heart leads him to help his family by planning the burial of his sick grandmother. In fulling his mission, he is bound to influence the lives of his townspeople and change the dim perspective of his family by proving that everything is possible if only one will see through the eyes of a child.
Two discs in one container.
Summary taken from container insert.
Production design by Gerry Santos ; film editing by Manet A. Dayrit ; music by Lutgardo Labad ; film editing, Manet A. Dayrit
Jiro Manio (Magnifico) ; Lorna Tolentino ; Albert Martinez ; Tonton Gutierrez ; Gloria Romero ; Celia Rodriguez ; Amy Austria ; Danilo Barrios (Miong) ; Mark Gil ; Cherrie Pie Picache ; Girlie Sevilla (Isang) ; Alison VII ; Jon Romano ; Susan Africa ; Isabella De Leon (Helen) ; Dindin Llarena ; Joseph Robles (Carlo).
In Tagalog.
Received Record Breaking 7 awards for best picture in 2004; Grand Prix Award for best picture at Rome Internationale Children's Film Festival, best film at Rome Children International Film Festival in 2005, International Grand Jury Award at Madrid Children and Youth Film Festival in 2005, and Audience Award at Sheffield Children and Youth Film Festival in 2005